2009
DOI: 10.1074/jbc.m109.050468
|View full text |Cite
|
Sign up to set email alerts
|

PGRL1 Participates in Iron-induced Remodeling of the Photosynthetic Apparatus and in Energy Metabolism in Chlamydomonas reinhardtii

Abstract: PGRL1 RNA and protein levels are increased in iron-deficient Chlamydomonas reinhardtii cells. In an RNAi strain, which accumulates lower PGRL1 levels in both iron-replete and -starved conditions, the photosynthetic electron transfer rate is decreased, respiratory capacity in iron-sufficient conditions is increased, and the efficiency of cyclic electron transfer under iron-deprivation is diminished. Pgrl1-kd cells exhibit iron deficiency symptoms at higher iron concentrations than wild-type cells, although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
84
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 60 publications
8
84
1
Order By: Relevance
“…It also shows that, like PGRL1 (Petroutsos et al, 2009;Tolleter et al, 2011) Figure 1A shows that an absence of PGR5 results in reduced photosynthetic growth and ultimately, light sensitivity when the cells are grown on minimal medium in air. When the atmosphere is enriched with 2% CO 2 or the medium is supplemented with acetate, the photosensitivity of pgr5 is relieved, which is shown in Figure 1B; growth of the mutant and wild-type lines is similar at a light intensity of 300 mmol photons m 22 s 21 .…”
Section: Reinhardtii Pgr5 Participates In Npq and Cefmentioning
confidence: 99%
See 2 more Smart Citations
“…It also shows that, like PGRL1 (Petroutsos et al, 2009;Tolleter et al, 2011) Figure 1A shows that an absence of PGR5 results in reduced photosynthetic growth and ultimately, light sensitivity when the cells are grown on minimal medium in air. When the atmosphere is enriched with 2% CO 2 or the medium is supplemented with acetate, the photosensitivity of pgr5 is relieved, which is shown in Figure 1B; growth of the mutant and wild-type lines is similar at a light intensity of 300 mmol photons m 22 s 21 .…”
Section: Reinhardtii Pgr5 Participates In Npq and Cefmentioning
confidence: 99%
“…Anoxia reduces the redox poise of the stroma, which has been shown to enhance CEF [measured in the presence of 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU)] in the wildtype line but not pgrl1 mutant cells (Tolleter et al, 2011). Furthermore, pgrl1 knockdown lines exhibited hypersensitivity to iron deficiency, linking iron limitation to formation/remodeling of the supercomplex associated with CEF (Petroutsos et al, 2009). Here, it was also shown that conformational changes occur to the PGRL1 protein in relation to the redox state and the presence and absence of iron ions, suggesting that the protein binds iron.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, cyanobacterial genomes do not contain a pgrl1 gene, which has been shown to be important for FQR-mediated CET in chloroplasts of plants 32,33 and green algae, 39,40 indicating that evolutionary differences also exist in the Photosynthesis Control mechanism.…”
Section: Pgr5-dependent Cet and Photosynthesis Controlmentioning
confidence: 99%
“…33 According to the commonly accepted view, the PGR5-PGRL1 dependent CET is assumed to sustain the ratio between ATP and NADPH (ATP/NADPH D 3/2), required for CO 2 fixation in the CalvinBenson-Bassham cycle. [34][35][36] However, the detailed characterization of pgr5 and pgrl1 mutants in Arabidopsis thaliana (hereafter: Arabidopsis), 31,32,34 and more recently in rice 37,38 and Chlamydomonas reinhardtii (hereafter: Chlamydomonas), [39][40][41][42] has allowed to associate novel functions to CET.…”
Section: Pgr5-dependent Cet and Photosynthesis Controlmentioning
confidence: 99%